An Automatic Contrast Validation Approach for Smartphone Themes - Khurshid, Aasim; Gil, Adriano; Guimarães, Felipe Augusto Souza; Gadelha, Mikhail; Fernandes, Everlandio (Anais Estendidos da Conference on Graphics, Patterns and Images (SIBGRAPI); 2020: Anais Estendidos da XXXIII Conference on Graphics, Patterns and Images, 2020)
The smartphone themes submitted to the themestore are first evaluated by human experts to ensure a pleasant visual experience1. One of the main challenges in smartphone themes evaluation is to validate the contrast of the elements of the theme. Contrast refers to the difference in visual properties that makes an object distinguishable from other objects and the background. In this work, we propose an automatic themes evaluation approach that validates the contrast of Android smartphone themes among regular and non-regular at the element level. To localize the contrast affected regions, the proposed themes evaluation is divided into two phases: 1) Element extraction; and 2) Contrast evaluation. For element extraction, a customized framework is created that utilizes native Android frameworks. Following, these elements are analyzed by using a specifically designed Convolutional Neural Network (CNN) for smartphone theme elements contrast evaluation. The proposed approach is evaluated on two databases which are composed of using the real Android themes. Experiments suggest that our proposed contrast-detection network can obtain a better performance than the known state-of-the-art classification methods, in smartphone themes evaluation, based on evaluation measures like Accuracy, F1 score, processing time and others.